1983
DOI: 10.1128/mcb.3.3.391-398.1983
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Alterations Associated with Overproduction of Asparagine Synthetase in Albizziin-Resistant Chinese Hamster Ovary Cells

Abstract: The amino acid analog albizziin was used to isolate Chinese hamster ovary cell lines which overproduce asparagine synthetase. Mutants selected in a single step after ethyl methane sulfonate mutagenesis were approximately 10-fold more resistant to the drug than the parental lines and expressed 8- to 17-fold elevations in enzyme activity. The karyotypes of these lines show alterations such as breaks and translocations affecting the long arm of chromosome 1. Cell lines isolated in several steps by growth in progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…We have previously described biochemical studies on AS regulation (4) and genetic characterization of AlbR and I-AHAR cells that overproduce AS activity (2,3,6). We have begun a molecular analysis of the mutant lines and found that AlbR cells have amplified copies of the gene for AS, whereas P-AHAR cell lines with high levels of resistance have no increase in AS copy number.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously described biochemical studies on AS regulation (4) and genetic characterization of AlbR and I-AHAR cells that overproduce AS activity (2,3,6). We have begun a molecular analysis of the mutant lines and found that AlbR cells have amplified copies of the gene for AS, whereas P-AHAR cell lines with high levels of resistance have no increase in AS copy number.…”
Section: Discussionmentioning
confidence: 99%
“…We have also investigated the role of DNA methylation in the expression of AS activity in drug-resistant mutant cell lines that overproduce the enzyme (2,3,6). Single-step mutant lines resistant to the amino acid analog P-aspartyl hydroxamate (P-AHAR) exhibit elevations in AS activity up to 8-fold over that of the parental cells (6,11), and multistep 1-AHAR lines express as high as 20-fold increases in AS activity (6).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…One aspect of the amplification process which varies from cell line to cell line is whether the amplified sequences are localized to a chromosome or are found extrachromosomally. For example, although exceptions exist (2,12,20), amplification in mouse cells tends to be extrachromosomal, whereas it is usually within chromosomes in hamster cells (for reviews, see references 6, 8, 19, and 39). While it is generally believed that some feature of the different cell lines in which gene amplification has been observed determines the cytogenetic outcome of the amplification process, this conclusion is mainly based on a comparison of the results obtained for the amplification of different genes in different cell lines.…”
mentioning
confidence: 99%